Jihad pena dan lidah: Sastra dan bahasa arab sebagai pilar perlawanan nasionalisme islam - samirah, samirah samirah (Maliki Interdisciplinary Journal, 2025)
This article explores how Arabic literature and language became crucial pillars in the struggle for Islamic nationalism through the concept of jihad of the pen and tongue. The background for this study stems from the understanding that jihad is not only a form of physical resistance but also encompasses intellectual and cultural struggle. The main problem addressed in this paper is how Arabic language and literary works were used to maintain Islamic identity and awaken the awareness of the Muslim community against colonialism and foreign cultural domination. The method employed is a literature review with a qualitative-descriptive approach to the works of scholars, Muslim literary figures, and relevant socio-religious phenomena. This article demonstrates that Arabic literature and the consistent use of the Arabic language have been effective media in articulating Islamic values, shaping public opinion, and strengthening Islamic intellectual networks. The analysis reveals that the jihad of the pen and tongue has had a significant impact on reinforcing the spirit of non-violent resistance, expanding Islamic influence in public discourse, and preserving the continuity of Islamic intellectual tradition up to the current digital era.